The Needs for Main Facilities and Availability of the Capture Fisheries Production in Cilacap Oceanic Fishing Port until 2027 - Ernani Lubis; Pujiono Pujiono (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightThe main facilities in Cilacap oceanic fishing port were identified and analyzed.Provide crucial information for the managers of the Cilacap oceanic fishing port with regards to developing the facilities.The predictions for the production of capture fisheries until 2027 in Cilacap oceanic fishing port have been analyzed to give the information to develop facilities capacity of the fishing port.AbstractFishing ports are an important factor in supporting various capture fisheries activ- ities in Indonesia. The number of vessels that landed fish at Oceanic Fishing Port (PPS) Cilacap during 2005-2013 increased by an average of 1.33% annually, which has implications for port capacity. It is important to know the capacity requirements for the basic facilities of the dock, and port pond at PPS, therefore that the activity of landing fish catches can take place properly. The purpose of this research is to not only get an overview of the current condition, and capacity of the main facil- ities at PPS Cilacap, but also to predict the production of fish caught until 2027. The research method is a case study. The data used in this study are primary, and secondary data obtained from PPS Cilacap. The results showed that the length of the landing dock in 2016 was 648.8m with the area, and depth of the port pool of 155,000 m2 and -2.5 m. The predicted requirement for the length of the landing dock until 2027 is 1,380.1 m, with the area and depth of the harbor pool of 239,612 m2 and -4.1 m. Based on the results, it shows that PPS Cilacap requires additional capacity of the dock, and port pool. Predictions of fish catch in 2022, and 2027 are 20,104,259 tons and 25,407,506 tons.